ANÁLISIS COMPARATIVO DEL CONSUMO ENERGÉTICO Y SEGURIDAD ELÉCTRICA EN VIVIENDAS DE QUEVEDO INSTALADAS CON Y SIN CUMPLIMIENTO DE NORMAS VIGENTES EN ECUADOR - PÉREZ VACA , PEDRO DANIEL (2025)
This research study addressed the issue of energy consumption and electrical safety in homes in the city of Quevedo, Ecuador, comparing homes installed under current regulations with those that do not comply with such regulations